(untitled) (Orfeu, 2021)
This article presents some results of the project “Creative listening as a methodological approach to the teaching of music in basic education” (PIBIC / UFMG / PRPq / 2019), which was developed in the Arts classes in a public school in Belo Horizonte, MG. The proposal consisted of the elaboration and application of eight didactic plans involving creative listening activities (DELALANDE, 2019; PAYNTER, 2010) in dialogue with other artistic languages (CAZNOK, 2008; SCHAFER, 2011). The data collected through observations, filming, photographs and interviews with young people and with the Arts teacher, revealed that creative listening proved to be a way to expand the musical repertoires and the musical development of young people. The strategy of integrating music with other artistic languages ​​provided different modes of musical enjoyment and enabled a greater engagement of young people with the activities proposed during classes.